header bg

Question:

Solve for y:
6(y+3) = 48

A y = 5
Explaination

We will first eliminate the parenthesis from the equation by using the distributive law. We will then isolate the variable on the left-hand side by carrying out the necessary mathematical operations on both sides of the equation. Finally, we will simplify the numbers to solve the equation for y.
Step 1:
Eliminate the parenthesis
We will apply the distributive law by multiplying both the terms in parenthesis by 6. This will eliminate the parenthesis from the equation.
6 × y + 6 × 3 = 48
Or, 6y + 18 = 48
Step 2:
Isolate the variable
We will first subtract 18 from both sides of the equation and carry out the subtraction.
6y + 18 – 18 = 48 – 18
Or, 6y = 30
We will then divide both sides of the equation by 6 to isolate y on the left-hand side, before simplifying the numbers to solve the equation.
(6y)/6 = 30/6
Or, y = 5